Parasites that cause problems in Malaysia: soil-transmitted helminths and malaria parasites - Balbir, Singh; Cox-Singh, J. (Elsevier Science Ltd, 2001)
Malaysia is a developing country with a range of parasitic infections. Indeed, soil-transmitted helminths and malaria parasites continue to have a significant impact on public health in Malaysia. In this article, the prevalence and distribution of these parasites, the problems associated with parasitic infections, the control measures taken to deal with these parasites and implications for the future will be discussed.